Primer of Jungian psychology - Hall, Calvin S. (Mentor New YorkUS, 1973)
Chronicles the highlights of Carl Jung's life and outlines his concepts on the structure, dynamics and development of normal human personality. Includes Jung's eight personality types, his theory of symbolism, and his views on dreams.